Insecticide toxicity, glutathione transferases and carboxylesterase activities in the larva of the Aedes mosquito - Shamaan, N.A.; Hamidah, R.; Jeffries, J.; Hashim, A.J.; Ngah, W.Z.Wan (Elsevier, 1993)
1. Toxicity evaluations of DDT, lindane, abate and carbaryl were carried out in the larvae of two wild Aedes aegypti strains from Kuala Lumpur and Klang. The Kuala Lumpur strain was more susceptible to the insecticides than the Klang strain. 2. The lethal toxicity time was also determined. The insecticides were found to take a longer time to exert their effect in the Klang strain as compared to the Kuala Lumpur strain. 3. Carboxylesterase activity was determined to be higher in the Kuala Lumpur strain, but glutathione transferase activities were higher in the Klang strain.